Medical Image Fusion Schemes Using Contourlet Transform and PCA Bases - Nithya, R.; S. Elayaraja (Asian Journal of Electrical Sciences, 2015)
Fusion imaging is one of the most modern, accurate and useful diagnostic techniques in medical imagin g today. The new technology has made a clear difference in patient care by compressing the time between diagnosis and treatment. Although image fusion can have different purposes, the main aim of fusion is spatial resolution enhancement or image sharpening. Also known as integrated imaging, it provides a computer link that allows for the combination of multimodal medical images into a single image with more complete and accurate description of the same object. The benefits are even more profound in combining anatomical imaging modalities with functional ones. For example, PET-CT in lung cancer, MRI-PET in brain tumors, SPECT-CT in abdominal studies and ultrasound images-MRI for vascular blood flow . outcome of MRI-CT image fusion has been shown to be able to assist in planning surgical procedure. Mainly, medical image fusion try to solve the issue of where there is no single modality provides both anatomical and functional information. Further more information provided by different modalities may be in agreement or in complementary nature.